The EU proposal for country-by-country reporting on the internet: Costs, Benefits and Consequences - Verena K. Dutt; Christoph Spengel; Heiko Vay (Stiftung Familienunternehmen, 2021)
As a result of the confidential sharing of data among tax authorities in different jurisdictions, effective tax rates have risen by between one and two percentage points. This demonstrates that the rules in place are working. By contrast, the publication of sensitive corporate data online makes no clearly verifiable contribution to the fight against tax evasion, money laundering and terrorism financing. On the contrary, it can result in unjustified competitive disadvantages for the companies concerned. This is one of the conclusions drawn by a study commissioned by the Foundation for Family Businesses and conducted by the Leibniz Centre for European Economic Research (ZEW).
Keywords: 330